2010
DOI: 10.1111/j.1751-1097.2010.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum‐specific Damage and Solar Ultraviolet Radiation Avoidance in the Two‐spotted Spider Mite

Abstract: The spatial distribution of the two-spotted spider mite Tetranychus urticae Koch is biased toward the lower surfaces of leaves as compared with the upper leaf surfaces on their host plants. Because of the deleterious effects of solar ultraviolet (UV) irradiation, we hypothesized T. urticae remains on lower leaf surfaces as an adaptation to avoid solar UV radiation (UVR). We examined the effects of solar UVR components on females and tested whether spatial distribution was associated with solar UVR avoidance. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 30 publications
2
74
0
2
Order By: Relevance
“…While cited reports point to the reaction of stressed plants, there could be a direct light influence on herbivores. For instance, UVA and UVB radiation have an effect on mite survival, reproduction, and spatial distribution on host-plants (Ohtsuka and Osakabe 2009;Sakai and Osakabe 2010). It was also determined that visible light treatment after UVB treatment caused photoreactivation of adult females, resulting in the increased survival recovery of T. urticae and Tyrophagus putrescentiae (Santos 2005), and effects on the egg hatchability of T. urticae as well as predatory mite (Koveos et al 2017;Murata and Osakabe 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While cited reports point to the reaction of stressed plants, there could be a direct light influence on herbivores. For instance, UVA and UVB radiation have an effect on mite survival, reproduction, and spatial distribution on host-plants (Ohtsuka and Osakabe 2009;Sakai and Osakabe 2010). It was also determined that visible light treatment after UVB treatment caused photoreactivation of adult females, resulting in the increased survival recovery of T. urticae and Tyrophagus putrescentiae (Santos 2005), and effects on the egg hatchability of T. urticae as well as predatory mite (Koveos et al 2017;Murata and Osakabe 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies demonstrated that solar UVB radiation also largely affected the behavior of spider mites (Ohtsuka and Osakabe 2009;Sakai and Osakabe 2010) and phytoseiid mites (Onzo et al 2010), and possibly restricted their foliar surface availability. Since Phytoseius nipponicus Ehara was the phytoseiid mite species commonly observed on VEP (Sudo et al 2010) and that preyed upon B. obovatus eggs (M. Sudo, unpublished data), it is likely that P. nipponicus was also vulnerable to UVB radiation as well as other phytoseiid mites.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effects of solar UV radiation on survival and spatial distribution between the upper and lower leaf surfaces have been investigated in herbivorous spider mites (Ohtsuka and Osakabe 2009;Suzuki et al 2009;Sakai and Osakabe 2010) and predaceous phytoseiid mites (Onzo et al 2010). 'Reverse gravity' experienced by inhabitants on the upper or lower leaf surfaces was also suggested to affect the distribution of a spider mite, i.e., mites preferred the leaf surface facing downward, regardless whether this was the morphological adaxial or abaxial side (Li and Margolies 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Avoidance of UV has been observed in bacteria (Bebout and Garcia-Pichel, 1995;Häder, 1987;Kruschel and Castenholz, 1998), protozoans (Barcelo and Calkins, 1979), nematodes (Edwards et al, 2008), echinoderms (Adams, 2001;Pennington and Emlet, 1986), amphibians (Han et al, 2007;Nagl and Hofer, 1997;van de Mortel and Buttemer, 1998), fish (Fukunishi et al, 2006;Holtby and Bothwell, 2008;Kelly and Bothwell, 2002), crustaceans (Barcelo and Calkins, 1979;Barcelo and Calkins, 1980;Storz and Paul, 1998), insects (Bothwell et al, 1994;Mazza et al, 1999;Mazza et al, 2002) and mites (Barcelo, 1981;Barcelo and Calkins, 1980;Onzo et al, 2010;Sakai and Osakabe, 2010;). In addition, mites are attracted to visible radiation (VIS) (Dimock and Davids, 1985;Hussey and Parr, 1963;McEnroe and Dronka, 1966;McEnroe and Dronka, 1969;Mori, 1962;Naegele et al, 1966;Suski and Naegele, 1963a;Suski and Naegele, 1963b).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have proposed that this location protects mites from fluctuations of air temperature (Gutierrez and Helle, 1985), rain (Gutierrez and Helle, 1985;Jeppson et al, 1975) and the deleterious effects of ultraviolet radiation (UV) (Barcelo, 1981;Ohtsuka and Osakabe, 2009;Sakai and Osakabe, 2010;, which leaves absorb and reflect (Smith, 1986).…”
Section: Introductionmentioning
confidence: 99%